90: HOSPITAL VARIATION IN FAILURE TO CURE IN ESOPHAGEAL CANCER SURGERY: IS THE PROPORTION OF PATIENTS UNDERGOING SURGERY PER HOSPITAL PIVOTAL?. (23rd April 2022) - Voeten, D M; Vissers, P A; Verhoeven, R H; Van Hillegersberg, R; Van Berge Henegouwen, M I
Abstract: Background and aim: The proportion of potentially curable esophageal cancer patients undergoing surgery varies among hospitals. Failure to cure is a composite outcome describing surgery not meeting its aim: (1) non-resectional surgery, (2) non-radical surgery (R1/R2) or (3) postoperative mortality. This study hypothesized that hospitals offering surgery to many patients have higher failure-to-cure rates. It aimed to investigate the relationship between the proportion of potentially curable esophageal cancer patients undergoing surgery and failure-to-cure rates. Methods: From the Netherlands Cancer Registry, all patients with cT1-cT4a/cTx-any cN-cM0 esophageal cancer diagnosed in 2015–2018 were included. For each region surrounding a surgical center, the expected proportion of patients undergoing surgery was established using multivariable analyses and divided by the observed proportion computing the O/E ratio. Hospitals were categorized into tertiles based on their tendency to treat patients surgically (O/E ratio). The association between these hospital groups and failure to cure was investigated using multilevel multivariable regression analyses. Results: In total, 3, 437 (53.2%) of 6, 457 potentially curable patients underwent surgery, ranging from 45–64% among 16 hospitals. The overall failure-to-cure rate was 15.0% (hospital variation [4.6%–23.7%]). After categorizing, 1, 003 patients underwent surgery in hospitals treating relatively few patients surgically (O/E ratio < 0.94), 1, 297 patients in average hospitals and 1, 137 patients in hospitals treating many patients surgically (O/E ratio > 1.01). Failure-to-cure rates were 16.8%, 12.2% and 14.0%, respectively. This was non-significant in multilevel analyses (aOR:0.63, 95%CI:0.38–1.05; aOR:0.76, 95%CI:0.46–1.24) (Table 1). Conclusion: Failure-to-cure rates were not significantly higher in hospitals with a high percentage of surgery, suggesting that increasing the surgery rate may be beneficial. Table: http://uploadfile.sem-2000.it/OLC/file/9203828791100911681076702/93673_Table.JPG .